Estimation Of Laterite Nickel Resources Using The Inverse Distance Weight Method PT Premlog Offshore Indonesia Kolaka Regency, Southeast Sulawesi Province - Ardi, Ardi; Jafar, Nurliah (Journal of Geology and Exploration, 2024)
Laterite nickel deposits are ores produced from the weathering process of ultraalkaline rocks on the earth's surface. The term laterit itself is taken from the Latin word "later" which means red brick. Mineral resources are a concentration or occurrence of materials that have economic value on or above the earth's crust, with certain shapes, qualities, and quantities that have a reasonable prospect to eventually be extracted economically. The purpose of this study is to determine the distribution of laterite nickel and calculate the number of resources at PT Premlog Offshore Indonesia. estimate the laterite nickel resources using the Inverse Distance Weighted method. In this study, the activities carried out are for modeling and estimation of laterite nickel resources using the inverse distance weighting (IDW) method. The creation of block models is done through the model block feature in the Surpac 6.5.1 program. The research is carried out directly in the field by taking documentation in the research area. Based on the results obtained from 19 drill points, a volume of 171,540 m³ and a tonnage of 257,310 tons with a COG of 1.5%. The density of nickel ore material at PT Premlog Offshore Indonesia is 1.5 tons/m3. Based on the research conducted at the research site, it can be concluded that in the Shapire Block area with a volume of 171,540 m3, the average Ni level is 1.8% with a nickel ore material density at PT Premlog Offshore Indonesia is 1.5 tons/m3, the indicated resource tonnage of 257,310 tons is obtained from the number of drill points as many as 19 with a drill point spacing of 50 m and COG 1.5 percent.